A bioinformatic analysis of microRNAs role in osteoarthritis. Issue 8 (August 2017) - Cong, L.; Zhu, Y.; Tu, G.
Summary: Objective: To evaluate the underlying function of microRNAs (miRNAs) in osteoarthritis (OA). Design: A bioinformatic analysis of miRNAs-OA studies was completed in multiple databases. All identified articles were assessed using specific inclusion and exclusion criteria (Eligible case–control studies for the present study included those which investigated miRNAs differential expression in cartilage tissues and cells of OA and controls. Abstracts, case reports, conference presentations, editorials, and expert opinions were excluded.). We performed bioinformatic analysis and assessed which miRNAs are commonly elevated or decreased in cartilage of OA, and assessed putative targets of these miRNAs using TargetScan, Database for Annotation, Visualization and Integrated Discovery (DAVID), FunRich and String. Results: Fifty seven studies were included in this study. Our current review has identified 46 differentially expressed miRNAs involved in autophagy, inflammation, chondrocyte apoptosis, chondrocyte differentiation & homeostasis, chondrocyte metabolism and degradation of the extracellular matrix (ECM). Additionally, our literature search identified a wide range of miRNAs that have been shown to be differentially expressed in OA. The function of up-regulated miRNAs primarily target nucleus, whereas the function of down-regulated miRNAs primarily target transcription. Conclusions: Comprehensive analysis of all miRNAs studies reveals cooperation in miRNA signatures and suggests that there may be two biologically synergic classes of miRNAs that are associated with OA. This finding suggests that miRNAs may be useful as diagnostic biomarkers and/or may provide new therapeutic targets in OA. Furthermore, a better understanding of the targets of these miRNAs will accelerate biomedical discoveries and improve clinical care based on new knowledge of OA-related disease mechanisms.